Health status, late effects and long‐term survivorship of allogeneic bone marrow transplantation: a retrospective study. Issue 2 (February 2014) - Gifford, G.; Sim, J.; Horne, A.; Ma, D.
Abstract Background Survival after allogeneic haemopoietic stem cell transplantation (allo‐HSCT) has improved because of advancements in allo‐HSCT. Allo‐HSCT has been performed in Australia since the late 1970s. However, there are few published data about health problems of allo‐HSCT survivors in Australia. Aims Identify health issues in long‐term survivors of allo‐HSCT in an Australian centre to manage better and prevent long‐term complications. Methods The health records of all patients of allo‐HSCT in a single centre from January 2000 to December 2007 and survived beyond 2 years were assessed. Results Ninety‐nine of the 200 allo‐HSCT patients survived beyond 2 years, and the median time from allo‐HSCT was 74 months. Twenty‐eight per cent died at a median of 37 months after allo‐HSCT because of relapsed malignancy (12%), stroke (1%), infection (3%), chronic graft versus host disease (9%), secondary malignancy (2%) and unknown cause (1%). Ninety‐one per cent reported one or more chronic health conditions. Health issues were chronic graft versus host disease (70%); respiratory (66%), ophthalmic (40%), bone (33%), and renal (26%) problems; and malignancies (14% skin, 3% solid organ). Seventy‐nine per cent resumed vocation at full or reduced capacity 2 years after allo‐HSCT. Clinicians identified 40% with quality of life (QOL) issues, but survivors' self‐reported QOL was comparable with the general Australian population. Conclusion This study shows that allo‐HSCT patients are living with high burdens of chronic diseases that warrant lifelong surveillance and engagement with healthcare. Structured, multi‐disciplinary care as recommended by published guidelines for allo‐HSCT survivors may reduce long‐term effects and improve their outcomes.